2020
DOI: 10.1002/jbmr.4048
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fall Biomechanics on Risk for Hip Fracture in Older Adults: A Cohort Study of Video-Captured Falls in Long-Term Care

Abstract: Over 95% of hip fractures in older adults are caused by falls, yet only 1% to 2% of falls result in hip fracture. Our current understanding of the types of falls that lead to hip fracture is based on reports by the faller or witness. We analyzed videos of real-life falls in longterm care to provide objective evidence on the factors that separate falls that result in hip fracture from falls that do not. Between 2007 and 2018, we video-captured 2377 falls by 646 residents in two long-term care facilities. Hip fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 44 publications
(89 reference statements)
1
37
0
Order By: Relevance
“…These results indicated that there are different mechanisms underlying different fall scenarios. As suggested in some previous studies, hip protectors [39, 40] which have not become popular in the Chinese mainland are effective in preventing hip fractures, and corner cushions could prevent harm from sharp furniture during falls. The supply of these protective devices should be guaranteed, and the use of them should also be advocated among residents with a high risk of falling.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…These results indicated that there are different mechanisms underlying different fall scenarios. As suggested in some previous studies, hip protectors [39, 40] which have not become popular in the Chinese mainland are effective in preventing hip fractures, and corner cushions could prevent harm from sharp furniture during falls. The supply of these protective devices should be guaranteed, and the use of them should also be advocated among residents with a high risk of falling.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…40 The load that the femur is subjected to depends on factors specific for the faller, such as soft tissue thickness over the greater trochanter, 3,44 stiffness, 42 and shape, 9 but also on biomechanical aspects of the fall such as impact velocity, impact region, and impact direction. 6,14,28,40,50,51 While hip protectors have been implemented to attenuate impact forces in case of a fall, 9,29,42,47,49 clinical studies investigating their effectiveness have revealed conflicting results. 24,45 One contributing factor may relate to hip protector design.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study was to find a best model to classify injurious versus non-injurious falls using sEMG data of hip muscles during a fall, and the injurious falls were defined based on previous studies, where a. the risk of hip fracture increases Table 3. [7], and b. hip impact force increases 60% (thereby hip fracture risk increases) when the impacting-side knee is free of constraint ("free knee" -neither the ground nor the contralateral knee contacts the impacting-side knee) at the time of hip impact [6]. We found that classification of initial fall direction through sEMG of hip muscles was not promising, and the accuracy of the best model was less than 50%.…”
Section: Discussionmentioning
confidence: 87%
“…During falls, activity of the iliopsoas, gluteus maximus and medius, and adductor longus were recorded from the EMG electrodes placed on the belly of the muscles. In this study, injurious falls were defined as falls involved "free knee", or "backward initial fall direction" based on two previous studies -Lim and Choi [6] and Yang et al [7], respectively.…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation